Gambaran Pola Asuh Pada Balita Stunting Dan Non Stunting Dilawe Desky Tongah - Pastika Adriana; Afnijar Wahyu (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for a long time, this causes disorders in the future, namely experiencing difficulties in achieving optimal physical and cognitive development. Objective: to identify and analyze parenting patterns in stunted toddlers compared to non-stunted toddlers in Lawe Desky Tongah Village. Stunting, or dwarfism, is a nutritional problem that significantly affects children's growth and development, and can be influenced by various factors including parental parenting patterns. Method: this study uses a Quantitative and Descriptive approach. The sampling technique in this study was Total Sampling, but when the study was conducted, 30 respondents were present, so the sample in this study was 30 respondents. Data analysis used Univariate Analysis. Results: the study showed significant differences in parenting patterns between parents of stunted and non-stunted toddlers. Parents of stunted toddlers tend to have inadequate parenting patterns related to providing nutritious food, health monitoring, and developmental stimulation. In contrast, parents of non-stunted toddlers are generally more consistent in providing food that meets nutritional needs, paying attention to children's health regularly, and providing stimulation that supports children's cognitive and motor development. Conclusion: This study emphasizes the importance of a holistic approach in dealing with stunting, by considering parenting aspects as one of the key factors. Recommendations for policy and practice include increasing access to nutrition education, support for parents, and strengthening child health services at the community level.